Diversity of mammals in Cerro Páramo Miraflores Regional Park, Huila, Colombia: analysis of structure and composition - Díaz-B, Camila A.; Ladino-Moreno, Jose Luis (Therya Notes, 2024)
The lack of field studies on the biodiversity of the Cerro Páramo de Miraflores Regional Park (PRCPM), Colombia, highlights the importance of obtaining reliable information to improve its management as a protected natural area. To this end, we evaluated the structure and composition of the assemblage of terrestrial and flying mammals of the high Andean and sub-páramo. For the recording of terrestrial and flying small, medium, and large mammals, we set transects of 100 Sherman traps, 8 mist nets, and 39 camera traps in the high Andean and sub-páramo zones of the PRCPM. With the records obtained and indirect traces, we calculated the alpha and beta diversity indices (Fisher's Alpha, Simpson, Shannon-Wiener, Whittaker, and Morisita-Horn). We recorded 21 species; the most abundant species were Thomasomys dispar (22.5 %), T. baeops (13.75 %), and Sturnira erythromos (8.75 %). We also documented flagship species such as Tremarctos ornatus and Puma concolor, as well as new geographic distribution records of Neomicroxus bogotensis, T. prínceps, Cryptotis squamipes, and Histiotus montanus for the department of Huila. Both zones showed medium diversity (H' = 2.317 and 1.885), with species dominance (D = 0.8612 and 0.8209) and high species turnover (Bw = 0.75; IM-H = 0.32). The PRCPM highlands are home to species typical of conserved environments and diverse trophic guilds, which indicate a good state of conservation. The highest similarity in species richness was found with the Perijá and Chingaza mountain ranges, with less than 50 % of species shared among the 11 Colombian Andean páramos. Although its species composition partially matches other páramopáramos, it differs in the mammal assemblage structure.